The Impact of Hazardous Alcohol Use on Behavioral Healthcare Utilization Among National Guard Service Members. (15th April 2016) - van den Berk-Clark, Carissa; Balan, Sundari; Shroff, Manan V.; Widner, Greg; Price, Rumi Kato
ABSTRACT: Background : Prior research suggests that both posttraumatic stress disorder (PTSD) and alcohol abuse affect behavioral healthcare utilization among combat-exposed military populations. However, their interactive effect is not well documented, especially after experiencing psychological trauma. Objective : This study examined the role of hazardous alcohol use (i.e. repeated patterns of drinking which lead to harmful consequences) on behavioral healthcare utilization among service members stratified by past-year combat exposure. Method : This study utilized a sample of National Guard service members who participated in an in-depth survey 2–4 months after returning from Operation Enduring Freedom, Operation Iraqi Freedom, or Operation New Dawn deployments (2011–2013) ( n = 467). We examine the marginal effect (the change in the probability) of hazardous alcohol use on utilization while controlling for trauma exposure, PTSD and other potential covariates. Results : In the unadjusted logistic model, hazardous alcohol use reduced the probability of behavioral healthcare utilization by 77% among service members who had been exposed to combat within the past year. In the adjusted model, which controlled for socio-demographics (age, gender, and race), health status (PTSD symptoms, depression and physical health), and measures of stigma (perception of services as embarrassing or harmful to one's career or social networks), hazardous alcohol use further reduced the utilization probability by 302%. Conclusion/Importance : Although these findings require replication, they appear to demonstrate that when combat-exposed service members engaged in hazardous alcohol use at postdeployment, they were much less likely to utilize behavioral healthcare to manage their posttraumatic stress symptoms during this period.